2015
DOI: 10.1007/s12194-015-0328-z
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the performance of the planning system by use of AAPM TG 119 test cases

Abstract: Our objective in this study was to create AAPM TG 119 test plans for intensity-modulated radiation therapy (IMRT) and volumetric-modulated arc therapy (VMAT) in the Monaco planning system. The results were compared with the published studies, and the performance of the Monaco planning system was analyzed. AAPM TG 119 proposed a set of test cases called multi-target, mock prostate, mock head and neck and C-shape to ascertain the overall accuracy of IMRT planning, measurement, and analysis. We used these test ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…For 6 MV VMAT plan, DVH parameters are closely agreeing with several published data. [ 12 13 ] For 15 MV IMRT and 15 MV VMAT plan, DVH parameters are closely agreeing with the DVH results of the 6 MV IMRT and 6 MV VMAT delivery of the present study.…”
Section: R Esults and Discussionsupporting
confidence: 88%
“…For 6 MV VMAT plan, DVH parameters are closely agreeing with several published data. [ 12 13 ] For 15 MV IMRT and 15 MV VMAT plan, DVH parameters are closely agreeing with the DVH results of the 6 MV IMRT and 6 MV VMAT delivery of the present study.…”
Section: R Esults and Discussionsupporting
confidence: 88%
“…2015) were also achieved the goal as per TG119 [15,16]. PTV D5 should be less than 8300cGy present study overall results showed the value of 7963±65cGy.…”
Section: Results:-mentioning
confidence: 50%
“…[1417] In this work, small ionization chamber (Pinpoint) was used instead of larger ionization chamber (Farmer) which was used by other researchers. [141516] The main advantage of this small chamber is its use for increasing the accuracy, in particular, in high-dose gradient and edge of the fields. [18]…”
Section: Discussionmentioning
confidence: 99%
“…[567] Recently, researchers have done TG-119 protocol on different planning systems, different detectors, and LINAC machines with different photon energies and obtained different gamma criteria. [8910111213141516]…”
Section: Introductionmentioning
confidence: 99%